2013
DOI: 10.1071/zo13032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural weathering conditions on faecal cortisol metabolite measurements in the greater bilby (Macrotis lagotis)

Abstract: Natural weathering conditions can influence faecal cortisol metabolite (FCM) measurements in wildlife if fresh faeces cannot be collected immediately following defaecation. In this study, we evaluated this issue in a threatened Australian marsupial, the greater bilby (Macrotis lagotis). Fresh (<12 h since defaecation) faecal samples (n = 19 pellets per bilby) were collected one morning from seven adult bilbies kept in captivity. One control faecal sample (Day 1) from each bilby was immediately frozen. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…1 Individual fecal cortisol metabolite concentrations (ng/g net dry weight) in bilby subjected to adrenocorticotropic hormone (ACTH) challenge. Day of injection is depicted using vertical dashed line old) bilby feces are fairly stable to natural weathering conditions up to 13 days; that is, the FCMs in these feces are not deteriorated (Evans et al 2013). Therefore, our sampling methods using transects provide a reliable way of obtaining fresh bilby fecal samples that will eventually be used for indicating the physiological sensitivity of semi-free ranging populations against environmental threats such as stochastic weather events (storms and droughts) and predation by feral pests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Individual fecal cortisol metabolite concentrations (ng/g net dry weight) in bilby subjected to adrenocorticotropic hormone (ACTH) challenge. Day of injection is depicted using vertical dashed line old) bilby feces are fairly stable to natural weathering conditions up to 13 days; that is, the FCMs in these feces are not deteriorated (Evans et al 2013). Therefore, our sampling methods using transects provide a reliable way of obtaining fresh bilby fecal samples that will eventually be used for indicating the physiological sensitivity of semi-free ranging populations against environmental threats such as stochastic weather events (storms and droughts) and predation by feral pests.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed bilby fecal extracts for concentrations of FCM using enzyme immunoassay (EIA) previously described for other mammals (Wielebnowski et al 2002;Millspaugh and Washburn 2004), and recently used for a captive subpopulation of the greater bilby (Narayan et al 2012;Evans et al 2013). Laboratory validation was done using accuracyrecovery checks and parallelism.…”
Section: Fecal Sampling: Captivementioning
confidence: 99%
“…African elephant, Foley et al ., 2001 ; Iberian lynx, Jewgenow et al ., 2006 ; Vargas et al ., 2008 ; greater bilby, Narayan et al , 2012 ; koala, Narayan et al ., 2013b ). Despite such a strong emphasis on methodological validation, focus has somewhat been diverted away from the necessity to explore potential sources of error that can arise much earlier in the field sampling process, especially during sample collection and processing ( Barja et al ., 2012 ; Descovich et al ., 2012 ; Evans et al ., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hormone deterioration because of bacterial degradation in faeces is a major source of FCM variation ( Beehner and Whitten, 2004 ). In instances where samples cannot be collected immediately and preserved (such as remote field studies), bacterial enzymes present in the faeces have been reported to degrade or alter hormone metabolite concentrations in samples that are left untreated, which increases the variation in glucocorticoid metabolites ( Touma and Palme, 2005 ; Evans et al ., 2013 ). The increased variation owing to natural weathering effects on faecal samples exposed to the environment can confound results and minimize the reliability of non-invasive endocrine methods for use in field conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation